2014
DOI: 10.2174/156720501108140910122220
|View full text |Cite
|
Sign up to set email alerts
|

SIST-M-IR Activities of Daily Living Items that Best Discriminate Clinically Normal Elderly from those with Mild Cognitive Impairment

Abstract: Background Activities of daily living (ADL) impairment is a hallmark of Alzheimer's disease (AD) dementia, but impairment in instrumental ADL (IADL) has been reported in mild cognitive impairment (MCI). The Structured Interview and Scoring Tool-Massachusetts Alzheimer's Disease Research Center (MADRC)-Informant Report (SIST-M-IR) includes 60 graded items that assist in scoring the Clinical Dementia Rating; it assesses the spectrum of cognitive and ADL changes relevant to early AD. Of the 60 SIST-M-IR items, 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Several subjective IADL scales have been used to successfully distinguish between CN and MCI: the total score of the FAQ, the CDR, the Structured Interview and Scoring Tool—MADRC Informant Report (SIST-M-IR), the ADL-Prevention Instrument (ADL-PI), and the ECog [3,4,26–28]. Four of the SIST-M-IR items in particular have been shown to best discriminate between CN and MCI [29]. Moreover, the SIST-M-IR and ADL-PI total scores have been shown to successfully predict progression from CN to MCI and future cognitive decline in CN elderly [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Several subjective IADL scales have been used to successfully distinguish between CN and MCI: the total score of the FAQ, the CDR, the Structured Interview and Scoring Tool—MADRC Informant Report (SIST-M-IR), the ADL-Prevention Instrument (ADL-PI), and the ECog [3,4,26–28]. Four of the SIST-M-IR items in particular have been shown to best discriminate between CN and MCI [29]. Moreover, the SIST-M-IR and ADL-PI total scores have been shown to successfully predict progression from CN to MCI and future cognitive decline in CN elderly [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Research is increasingly focused on identifying AD at the MCI stage, or even earlier, in order to prompt interventions and to access clinical trials with disease-modifying drugs [ 41 ]. Clearly, higher-order functional activities have been shown to distinguish those at risk of developing MCI from those remaining cognitively normal [ 42 - 44 ]. Studies utilizing continuous, unobtrusively monitored in-home activity data in a community setting also showed that these ecologically valid activity measures could identify early changes among those who convert to MCI [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in cognitive and functional abilities can be detected in the prodromal or “mild cognitive impairment (MCI)” stage of dementia . Identifying the earliest symptoms of MCI is important for predicting progression to dementia and in providing a target for potential therapeutic interventions which act in the earlist stages of neurodegenerative diseases such as Alzheimer disease (AD) . Current clinical diagnostic criteria for MCI include problems in performing instrumental activities of daily living (IADL) as a part of the clinical syndrome .…”
Section: Introductionmentioning
confidence: 99%